Moderately high frequency ventilation with a conventional ventilator allows reduction of tidal volume without increasing mean airway pressure - Cordioli, Ricardo Luiz (Intensive Care Med Exp, 2014)
BACKGROUND: The aim of this study was to explore if positive-pressure ventilation delivered by a conventional ICU ventilator at a moderately high frequency (HFPPV) allows a safe reduction of tidal volume (V(T)) below 6 mL/kg in a porcine model of severe acute respiratory distress syndrome (ARDS) and at a lower mean airway pressure than high-frequency oscillatory ventilation (HFOV). METHODS: This is a prospective study. In eight pigs (median weight 34 [29,36] kg), ARDS was induced by pulmonary lavage and injurious ventilation. The animals were ventilated with a randomized sequence of respiratory rates: 30, 60, 90, 120, 150, followed by HFOV at 5 Hz. At each step, V(T) was adjusted to allow partial pressure of arterial carbon dioxide (PaCO(2)) to stabilize between 57 and 63 mmHg. Data are shown as median [P25th,P75th]. RESULTS: After lung injury, the PaO(2)/FiO(2) (P/F) ratio was 92 [63,118] mmHg, pulmonary shunt 26 [17,31]%, and static compliance 11 [8,14] mL/cmH(2)O. Positive end-expiratory pressure (PEEP) was 14 [10,17] cmH(2)O. At 30 breaths/min, V(T) was higher than 6 (7.5 [6.8,10.2]) mL/kg, but at all higher frequencies, V(T) could be reduced and PaCO(2) maintained, leading to reductions in plateau pressures and driving pressures. For frequencies of 60 to 150/min, V(T) progressively fell from 5.2 [5.1,5.9] to 3.8 [3.7,4.2] mL/kg (p < 0.001). There were no detrimental effects in terms of lung mechanics, auto-PEEP generation, hemodynamics, or gas exchange. Mean airway pressure was maintained constant and was increased only during HFOV. CONCLUSIONS: During protective mechanical ventilation, HFPPV delivered by a conventional ventilator in a severe ARDS swine model safely allows further tidal volume reductions. This strategy also allowed decreasing airway pressures while maintaining stable PaCO(2) levels.